Role of Teat Dipping After Milking for Subclinical Mastitis Control and Improving Production of Dairy Cow - Ardilasunu Wicaksono; Etih Sudarnika; Herwin Pisestyani; Mirnawati Sudarwanto; Abdul Zahid; Arifin Budiman Nugraha; Muhammad Pauzi Lubis; Iccha Pradipta Patsiwi (Buletin Peternakan, 2019)
This study was aimed to compare somatic cell count and milk production on dairy cattle after teat dipping post milking application. Samples collected from total of 121 quarters of dairy cattle in normal lactation period and identified as infected by subclinical mastitis. Subclinical mastitis examination was done by IPB Test Mastitis Test, somatic cell count calculation was done by Breed Method, and observation of milk production was done by calculating milk volume per quarter. Observations were performed during normal lactation periods of 12 weeks. Data were analyzed statistically using Mann-Whitney Test and unpaired t-test. The results showed that the number of somatic cells count in the treatment group with post milking teat dipping application was lower than in the control group and significantly different at week 11 (p = 0.039). Furthermore, the volume of milk production in the treatment group was higher than in the control group and significantly different in almost all weeks of observation (p<0.05). It was showed that post milking teat dipping application can prevent subclinical mastitis infection effectively, seen from low somatic cell count (below 400.000 cells/ml) and can maintain optimum milk production. So that, this application can increase the economic benefits for dairy farmers.